Measurement of residual elastic strain and lattice rotations with high resolution electron backscatter diffraction. - Britton, T; Wilkinson, A (2011)
A set of dynamically simulated electron backscatter patterns (EBSPs) for α-Ti crystals progressively rotated by 1° steps were analysed using cross-correlation to determine image shifts from which strains and rotations were calculated. At larger rotations the cross-correlation fails in certain regions of the EBSP where large shifts are generated. These incorrect shifts prevent standard least square error procedures from obtaining a valid solution for the strain and rotation, where the applied rotation exceeds ∼ 8°. Using a robust iterative fitting routine reliable strains and rotations can be obtained for applied rotations of up to and including ∼ 11° even though some image shifts are measured incorrectly. Finally, high resolution electron backscatter diffraction has been used to analyse the residual elastic strain, lattice rotations and density of stored geometrically necessary dislocations in a sample of copper deformed to 10% total strain. The robust iterative fitting analysis allows reliable analysis of a larger proportion of the map, the difference being most obviously beneficial in regions where significant lattice rotations have been generated.